Quantifying the release of tyre wear particles to the marine environment via multiple pathways. (November 2021) - Parker-Jurd, Florence N.F.; Napper, Imogen E.; Abbott, Geoffrey D.; Hann, Simon; Thompson, Richard C.
Abstract: Desk-based studies have suggested tyre wear particles contribute a substantial portion of microplastic emissions to the environment, yet few empirical studies report finding tyre wear. Samples were collected from three pathways to the marine environment: atmospheric deposition, treated wastewater effluent, and untreated surface runoff. Pyrolysis coupled to gas chromatography–mass spectrometry was used to detect benzothiazole, a molecular marker for tyres. Benzothiazole was detected in each pathway, emitting tyre wear in addition to other sources of microplastics. Release via surface water drainage was the principle pathway in the regions examined. Laboratory tests indicated larger particles likely settle close to their entry points, whereas smaller particles have potential for longer-range transport and dispersal. The previous lack of reports are likely a consequence of inadequate methods of detection, rather than a low environmental presence. Further work is required to establish distribution, transport potential, and potential impacts once within the marine environment. Graphical abstract: Unlabelled Image Highlights: Tyre wear reported as contributor to microplastic emissions, yet few studies report tyre wear in the marine environment. This study quantified tyre wear emissions at principle entry points to the marine environment using pyrolysis GC-MS. Surface runoff drainage appeared principle pathway of for tyre wear to the marine environment. Findings suggest tyre wear contamination is a major, additional, contributor to microplastic abundance in the environment.